A Novel Method for Assessment of the Velocity of Detonation for Primary Explosives. Issue 4 (20th February 2018) - Jafari, Mohammad; Keshavarz, Mohammad Hossein; Zamani, Ahmad; Zakinejad, Sajjad; Alekaram, Iman
Abstract: Primary explosives are hazardous energetic materials with considerable sensitivities to external stimuli such as impact, friction, flame, heat, electric spark, and shock. A novel correlation has been introduced for prediction of detonation velocities of different hazardous primary explosives. The needed data for the new model are the loading density, the heat of detonation, the sum of the moles of gaseous products per gram of explosive and the average molecular weight of gaseous products. Decomposition products were specified based on the oxygen balance of primary explosives. Cross‐validation of the model and the statistical parameters were used for evaluating the goodness‐of‐fit, goodness‐of‐prediction, accuracy, and precision of the new model. The statistical parameters of the new model, as compared to the outputs of one of the best available thermochemical computer codes, confirm the higher reliability of the new correlation. Abstract :